2015
DOI: 10.1016/j.jaci.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy of short and long thymic stromal lymphopoietin isoforms in inflammatory disorders of the bowel and skin

Abstract: BackgroundThymic stromal lymphopoietin (TSLP) is a cytokine with pleiotropic functions in the immune system. It has been associated with allergic reactions in the skin and lungs but also homeostatic tolerogenic responses in the thymus and gut.ObjectiveIn human subjects TSLP is present in 2 isoforms, short and long. Here we wanted to investigate the differential expression of the TSLP isoforms and discern their biological implications under homeostatic or inflammatory conditions.MethodsWe evaluated the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
162
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(181 citation statements)
references
References 42 publications
13
162
4
2
Order By: Relevance
“…Although TSLP mRNA expression has already been detected in healthy skin, its protein expression (Bjerkan et al, 2015;Fornasa et al, 2015) was found only in inflamed epidermis (AD, psoriasis) until now (Soumelis et al, 2002;Ziegler, 2012). The conflicting data between the previous publications and our current study might be explained by that the other investigators most probably used healthy SGP skin and no SGR samples as controls of AD or psoriasis.…”
Section: Discussioncontrasting
confidence: 70%
“…Although TSLP mRNA expression has already been detected in healthy skin, its protein expression (Bjerkan et al, 2015;Fornasa et al, 2015) was found only in inflamed epidermis (AD, psoriasis) until now (Soumelis et al, 2002;Ziegler, 2012). The conflicting data between the previous publications and our current study might be explained by that the other investigators most probably used healthy SGP skin and no SGR samples as controls of AD or psoriasis.…”
Section: Discussioncontrasting
confidence: 70%
“…A previous study showed that vitamin D3 induced increased transcription primarily of the sfTSLP isoform and that sfTSLP exerts anti-inflammatory effects in inflammatory disorders of the bowel19. In our previous results, we have found that 1,25D3 upregulated sfTSLP expression.…”
Section: Resultsmentioning
confidence: 53%
“…LfTSLP has 159 amino acids and sfTSLP encompasses the last 63 residues of lfTSLP and is identical to its C-terminal portion19. In normal human bronchial epithelial cells, two TSLP splice variants have been reported and lfTSLP, but not sfTSLP, was highly induced after exposure to polyinosinic-polycytidylic acid (polyI:C)20.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TSLP was found to downregulate filaggrin expression via activating the janus kinase-STAT3 pathway that influenced the skin barrier function [24,43]. The TSLP isoform (short/long) ratio is altered in several inflammatory disorders, which has implications for the treatment and prevention of AD [44]. However, attention in reducing TSLP synthesis or release as a therapeutic strategy is limited.…”
Section: Epidermal Tslp: a Factor Link Two Major Pathogenesis In Admentioning
confidence: 99%